Harnessing probiotic-metformin synergy: targeting the gut-microbiota metabolism axis to ameliorate polycystic ovary syndrome - Yang, Wanqiu; Yin, Lin; Xie, Qingling; Tan, Moyao; Liu, Yunzhu; Xu, Jili; Wu, Jie (Frontiers in Nutrition, 2026)
BackgroundPolycystic ovary syndrome (PCOS) and type 2 diabetes mellitus (T2DM) are interrelated through insulin resistance (IR) and gut microbiota dysbiosis. This review evaluates the synergistic efficacy and mechanisms of a combined probiotic and metformin regimen in the management of PCOS, with a specific focus on the gut-ovary-metabolism axis.MethodsA systematic literature search was conducted following PROSPERO (ID: CRD420251143914) registration across PubMed, EMBASE, Web of Science, the China National Knowledge Infrastructure (CNKI), the Wanfang Database, and the VIP Database, prioritizing randomized controlled trials and retrospective studies.ResultsThe combination therapy suggests improved outcomes compared to metformin monotherapy, yielding significant improvements in metabolic, hormonal, and reproductive function. Crucially, probiotics alleviated metformin-induced gastrointestinal adverse effects, thereby enhancing treatment adherence. The proposed underlying mechanisms involve a synergistic restoration of gut microbial homeostasis, increased production of short-chain fatty acids, reinforcement of the intestinal barrier, and potentiated activation of the AMP-Activated Protein Kinase (AMPK) pathway.ConclusionAs an adjunct supplement to metformin, probiotics represent a novel, evidence-supported therapeutic strategy for PCOS. This approach offers enhanced efficacy and tolerability, with potential implications for a broader spectrum of metabolic disorders including T2DM; however, given the current paucity of related studies, conclusions should be drawn cautiously.Systematic review registration[https://www.crd.york.ac.uk/prospero/], identifier [CRD420251143914].